CORRELATION OF CYSTOSTOMY TO LOW URETHROCUTANEOUS FISTULA INCIDENT IN HYPOSPADIA SURGERY - Laura, S. F.; Duarsa, G. W. K.; Mahadewa, T. G. (BALI MEDICAL JOURNAL, 2014)
Background: Hypospadia is the most common congenital abnormalities to the penis. The most common post-operative complications and hypospadias is uretherocutan fistula. Uretherocutan fistula is arising from an infected wound, hematoma, urinary extravasations, ischemic necrosis of the flap or graft, technical errors, and postoperative care. Although, reconstruction of the urethra without cystostomy results in patients discharged quickly, some sources still recommend the use of cystostomy in hypospadias surgery. This is because of lower complication rate and more comfortable for the children during the postoperative period. The purpose of this study was to determine the incidence of fistula uretherocutan correlation with cystostomy using hypospadia operation. Methods: This study was carried out with cross-sectional design involving 68 patients, comprising 34 people with operating groups and 34 other people of hypospadias surgery without cystostomy. This is a retrospective study by observing medical record of the patients at Sanglah General Hospital from December 2013 until May 2014. All data obtained were assayed with Chi-square and Person Correlation and considered significant at p < 0.05. Results: This Study reports that the value of r = -0.364, p = 0.034, and PR = 0.16. However, there is a correlation in the use of cystostomy to a lower incidence of fistula in operation uretherocutan hypospadia. In cystostomy surgery, fistula incidence was 2.9% and operating without cystostomy was 17.6%. In operation hypospadia using cystostomy is expected to reduce the incidence of fistula.